Endothelial β1 Integrin-Mediated Adaptation to Myocardial Ischemia - Henning, Carina; Branopolski, Anna; Follert, Paula; Lewandowska, Oksana; Ayhan, Aysel; Benkhoff, Marcel; Flögel, Ulrich; Kelm, Malte; Heiss, Christian; Lammert, Eckhard (Thrombosis and Haemostasis, 2021)
Background Short episodes of myocardial ischemia can protect from myocardial infarction. However, the role of endothelial β1 integrin in these cardioprotective ischemic events is largely unknown.Objective In this study we investigated whether endothelial β1 integrin is required for cardiac adaptation to ischemia and protection from myocardial infarction.Methods Here we introduced transient and permanent left anterior descending artery (LAD) occlusions in mice. We inhibited β1 integrin by intravenous injection of function-blocking antibodies and tamoxifen-induced endothelial cell (EC)-specific deletion of Itgb1. Furthermore, human ITGB1 was silenced in primary human coronary artery ECs using small interfering RNA. We analyzed the numbers of proliferating ECs and arterioles by immunohistochemistry, determined infarct size by magnetic resonance imaging (MRI) and triphenyl tetrazolium chloride staining, and analyzed cardiac function by MRI and echocardiography.Results Transient LAD occlusions were found to increase EC proliferation and arteriole formation in the entire myocardium. These effects required β1 integrin on ECs, except for arteriole formation in the ischemic part of the myocardium. Furthermore, this integrin subunit was also relevant for basal and mechanically induced proliferation of human coronary artery ECs. Notably, β1 integrin was needed for cardioprotection induced by transient LAD occlusions, and the absence of endothelial β1 integrin resulted in impaired growth of blood vessels into the infarcted myocardium and reduced cardiac function after permanent LAD occlusion.Conclusion We showed that endothelial β1 integrin is required for adaptation of the heart to cardiac ischemia and protection from myocardial infarction.
Keywords: endothelial β1 integrin; cardiac vascular growth; myocardial infarction; cardioprotection